Analisis Stabilitas Tanah Timbunan dengan Perkuatan Turap Kayu Galam di Daerah Rawa Kalimantan Selatan - Akhmad Gazali; Fathurrahman Fathurrahman (Media Ilmiah Teknik Sipil, 2019)
South Kalimantan is one of the areas that has a lot of swamps. The use of galam wood is an alternative to the construction of landslide resistors on the roadside in swamp areas. Landslides often occur on the edge of road piles in swamp areas. Not infrequently damage due to landslides on several roads. This study aims to determine the effect of galam wood plaster reinforcement on increasing soil carrying capacity and stability of embankment due to the operation of external forces. The factor of manual embankment slope safety with the fellenius slice method shows that SF = 0.857 <1.0 "is not safe" so there will be a collapse on the slope of the embankment. Then the embankment stability analysis is carried out gradually, so that an increase from cu = 1.04 t/m2 to cu = 1.8 t/m2. The results of the analysis carried out manually revealed that the total decrease was = 284.62 cm ≈ 285 cm. For the simulation results with the PLAXIS program, it shows that there is a decrease of 3.1 cm.